Operating Liquidity and Financial Leverage: Evidences from Indian Machinery Industry. (15th May 2015) - Goel, Utkarsh; Chadha, Saurabh; Sharma, Anil K.
Abstract: Operating liquidity and financial leverage are two significant aspects of overall firm management. This paper analyses the impact of financial leverage on various measures of operating liquidity. Further, we examine the effect of both operating liquidity and financial leverage on the firm's performance. We employ a sample of 151 Indian machinery firms and 10 years annual financial standalone data from 2004-05 to 2012-13 was collected using CMIE Prowess database. Ratio analysis and Panel data regression model have been applied to study the relationship. It was found that financial leverage has significant impact on different measures of operating liquidity. Further operating liquidity and financial leverage have considerable impact on performance of the Indian machinery firms. This study provides insights on interrelation between operation management and financial management and their impact on firm's performance.